Decalin-assisted light emitting porous Si formation and its optical, surface and morphological properties - Karatutlu, Ali; Istengir, Sumeyra; Cosgun, Sedat; Seker, Isa; Unal, Bayram (ELSEVIER SCIENCE BV, 2017)
In this research paper, light emitting porous silicon (Lep-Si) samples were fabricated by a surfactant-mediated chemical stain etching solution in order to form homogenous luminescent nanostructures at room temperature. As an industrially important solvent, decalin (decahydronaphtalene) was used as a surfactant in the HF/HNO3 solutions in order to control the etching process. Morphological, surface and optical properties of the Lep-Si samples were examined using atomic force microscopy, X-ray photoelectron spectroscopy, photoluminescence (PL) spectroscopy, and laser scanning confocal microscopy (LSCM) techniques. These characterization techniques were correlated with the various etching times including depth dependent luminescence profiles for the first time. We report the optimum conditions for production of the most efficient Lep-Si using decalin (decahydronaphtalene) and possible structural origins of light emission using the depth dependent luminescence measurements. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Lep-Si; Surfactant; Chemical etching; Photoluminescence; Confocal microscopy; SILICON SOLAR-CELLS; XPS; Chemistry; Materials Science; Physics